Dehydrocyclization of n-heptane over a PtBa/Kl catalyst: Reaction mechanism - Arcoya, Adolfo (2005)
The dehydrocyclization of n-heptane to toluene over a 1 wt.% PtBa/KL catalyst was studied in a fixed bed tubular reactor, at 723 K, 100 kPa and space-time in the range of 1.8-117.0 g h mol-1. The catalyst was prepared by incipient wetness impregnation of a KL zeolite, previously alkalized with BaO, using an aqueous solution of tetraammineplatinum(II) hydroxide as platinum precursor. The solid was successively calcined in an oxygen stream and reduced in flowing hydrogen, at 773 K. Reaction is highly selective towards toluene (>60%) at conversion levels even close to 100%, with benzene, heptenes, methylcyclohexane and ethylcyclopentane as major byproducts. From the product distribution and the dehydrocyclization results of the reaction products performed in separate experiments, a macroscopic mechanism is proposed. Essentially, n-heptane is adsorbed and transformed on the catalyst surface through an alkene-like intermediate (σC7=), following five possible parallel interconnected paths, involving hydrogenolysis, isomerization, dehydrogenation and cyclization reactions. Formation of toluene as a primary product is explained by a "rake scheme" in which the σC7= intermediate is successively transformed, following two possible routes: (a) C1-C6 ring closure and subsequent further dehydrogenation; (b) successive dehydrogenation to heptatriene and then cyclization to toluene. These transformations occur in the adsorbed phase and on the same active site, in such a way that only a small fraction of the total adsorbed intermediates formed appear in the gas phase. The rest are not desorbed due to their high reactivity.